Prosocial skeptics: Skepticism and generalized trust - Loveland, Matthew T. (Critical research on religion, 2017)
We report on a study of the religious correlates of generalized trust. Our critical frame leads us to explore novel questions about how nonreligion may encourage social trust. We find that those who believe the bible to be a book of fables are more trusting than those with other beliefs about the text, and that nontheists report a greater willingness to trust. We discuss the implications of our findings for future research about religious belief and generalized trust.